2010
DOI: 10.1007/978-3-642-14064-8_28
|View full text |Cite
|
Sign up to set email alerts
|

VerroTouch: High-Frequency Acceleration Feedback for Telerobotic Surgery

Abstract: Abstract. The Intuitive da Vinci system enables surgeons to see and manipulate structures deep within the body via tiny incisions. Though the robotic tools mimic one's hand motions, surgeons cannot feel what the tools are touching, a striking contrast to non-robotic techniques. We have developed a new method for partially restoring this lost sense of touch. Our VerroTouch system measures the vibrations caused by tool contact and immediately recreates them on the master handles for the surgeon to feel. This aug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
53
0
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 19 publications
(22 reference statements)
3
53
0
6
Order By: Relevance
“…By alternating the voltage, it was possible to modulate the friction force felt by the moving finger. A similar device has been presented in [14], where the authors developed a system, named VerroTouch, for providing cutaneous feedback to surgeons during telerobotic surgery. VerroTouch measured the vibrations caused by tool contact and recreates them on the master handles for the surgeon.…”
Section: Introductionmentioning
confidence: 99%
“…By alternating the voltage, it was possible to modulate the friction force felt by the moving finger. A similar device has been presented in [14], where the authors developed a system, named VerroTouch, for providing cutaneous feedback to surgeons during telerobotic surgery. VerroTouch measured the vibrations caused by tool contact and recreates them on the master handles for the surgeon.…”
Section: Introductionmentioning
confidence: 99%
“…This device can produce force feedback to the user and was implemented to facilitate the use of a surgical robot [10]. Here, force touch feedback sensations are used to help the operator of the robot to interact with the internal body parts encountered in minimally invasive surgery.…”
Section: Introductionmentioning
confidence: 99%
“…This feedback approach has been demonstrated via bench-top research devices [14,20], and has shown promise for both industrial [7] and medical applications [25,15,18]. This approach has also been investigated for improving the tactile sensitivity of hand-held (non-robotic) tools [26].…”
Section: Introductionmentioning
confidence: 99%